Predicting lubricant oil induced pre-ignition phenomena in modern gasoline engines: The reduced GasLube reaction mechanism. (1st December 2020) - Distaso, E.; Amirante, R.; Calò, G.; De Palma, P.; Tamburrano, P.; Reitz, R.D.
Highlights: A reduced reaction mechanism is developed to predict pre-ignition in modern gasoline engines. This so-called "GasLube" mechanism is validated for a wide range of operating conditions. A detailed study of the auto-ignition process of gasoline/oil mixtures is performed. A single pure species, n-Hexadecane, can serve as surrogate species for lubricant oil. The "GasLube" mechanism accurately predicts the reduction of gasoline ignition delay due to lubricant oil. Abstract: Recent research highlights the influence of the presence of lubricant oil droplets on the combustion process in Direct Injection Spark Ignition (DISI) engines. Lubricant oil is considered to be the main responsible agent for the onset of pre-ignition phenomena, which can escalate highly undesired super-knock events. Moreover, lubricant oil plays a primary role in the generation of very fine soot particle emissions. In the present work, a reduced reaction mechanism is developed for modeling the combustion of gasoline-oil mixtures, allowing one to simulate the variation in ignitability of gasoline-like fuels induced by the presence of lubricant oil. In this study, a single hydrocarbon species, namely n-Hexadecane (n-C16 H34 ), is shown to reproduce lubricant oil chemical and physical characteristics. Great effort has been performed to identify the most significant reaction pathways to reduce the complexity of the chemistry mechanism and the number of variables, while maintaining the important features of detailed mechanisms, for the highest computational efficiency. The proposed reduced mechanism has been validated for a wide range of operating conditions. It is employed for 3D simulations of experimental measurements in which iso -Octane was blended with different percentages of lubricant oil and its surrogates. Operating conditions representative of those of a typical turbocharged DISI engine are considered. The very good agreement obtained in the comparison with the experimental data confirms the effectiveness of the proposed "GasLube" mechanism in reproducing lubricant oil's influence on ignition propensity of gasoline-like fuels. Furthermore, the 3D numerical simulations allowed a detailed analysis of the ignition phenomenon, providing more insight into the basic processes of lubricant oil induced pre-ignition events in DISI gasoline engines.